Techno-economic analysis of innovative solutions for island grids with high renewable solar share - Dubey Abhishek; Sorce Alessandro; Rivarolo Massimo; Traverso Alberto; Sala Silvio (E3S Web of Conferences, 2023)
This paper presents a techno-economic analysis of a hybrid dispatch strategy on an island through conventional internal combustion engine (ICE) and innovative gas turbine (GT) with pressure gain combustion (PGC) in the presence of renewable solar-PV. Plant configurations with conventional technologies were defined based on established industrial data, and specifications of novel PGC-GT technology were estimated using the industrial data of conventional GT and on-design results available in the literature. Optimization of the operational strategy was conducted in WECoMP, a modular and flexible software tool developed by Thermochemical Power Group (TPG) at the University of Genova. The performance of different hybrid plants was analyzed in terms of annual production, fuel consumption, curtailment, CO2 emissions, cost, and sensitivity to fuel price. This is complemented by a parallel paper investigating the mechanical rotating inertia features of such prime movers, further supporting their suitability in enabling the integration of non-dispatchable renewables. Results showed that the 2-stroke ICE technology provided the best performance in terms of emissions and cost. Moreover, for all dispatchable prime movers, minimum LCOE occurred at an optimum value of PV capacity that facilitated annual CO2 reduction by 58.6 kton and LCOE reduction by 8.9 €/MWh. Finally, the optimum PV capacity was found to increase with fuel price, signifying the environmental benefits of high fuel prices.